Anaesthetic management for cleft palate in a child with digeorge syndrome: Look before you leap! - Sahoo, Sangeeta; Hansda, Upendra; Swaro, Swastika; Ahmad, Suma R (Indian Journal of Case Reports, 2019)
DiGeorge syndrome is a multisystem disorder associated with various cardiac anomalies, aplasia or hypoplasia of thymus and parathyroid glands, palatal defects, immune deficiency, and characteristic facial features. Here, we are reporting the case of a known DiGeorge syndrome posted for the repair of cleft palate in a 3-year-old female child. Anaesthetic management for any surgery in a child with DiGeorge syndrome is challenging for anaesthesiologist in terms of the associated complications. Hence, sound knowledge about DiGeorge syndrome is required for safe anaesthetic management.